2017
DOI: 10.1371/journal.pone.0173853
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the N-linked glycosites of rice (Oryza sativa L.) germinating embryos

Abstract: Germination is a key event in the angiosperm life cycle. N-glycosylation of proteins is one of the most common post-translational modifications, and has been recognized to be an important regulator of the proteome of the germinating embryo. Here, we report the first N-linked glycosites mapping of rice embryos during germination by using a hydrophilic interaction chromatography (HILIC) glycopeptides enrichment strategy associated with high accuracy mass spectrometry identification. A total of 242 glycosites fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…For example, a recent study reported a high abundance of PMGs (76.7% of the N ‐glycome) in ungerminated Oryza sativa seeds, which decreased dramatically to 36.1% after 48 h of germination (Horiuchi, Hirotsu, & Miyanishi, ). The PMGs were proposedly carried by vacuolar‐resident storage proteins utilised for growth and development during germination (Horiuchi et al ., ), and were further suggested to be synthesised and preserved in the rice germ until germination (Ying et al ., ). These findings suggest that GnT‐I, Hex and the other glyco‐enzymes facilitating PMP synthesis in plants (see Section II.1 a ) are active during seed development.…”
Section: Surveying Pmps Across the Eukaryotic Kingdoms And Phylamentioning
confidence: 97%
“…For example, a recent study reported a high abundance of PMGs (76.7% of the N ‐glycome) in ungerminated Oryza sativa seeds, which decreased dramatically to 36.1% after 48 h of germination (Horiuchi, Hirotsu, & Miyanishi, ). The PMGs were proposedly carried by vacuolar‐resident storage proteins utilised for growth and development during germination (Horiuchi et al ., ), and were further suggested to be synthesised and preserved in the rice germ until germination (Ying et al ., ). These findings suggest that GnT‐I, Hex and the other glyco‐enzymes facilitating PMP synthesis in plants (see Section II.1 a ) are active during seed development.…”
Section: Surveying Pmps Across the Eukaryotic Kingdoms And Phylamentioning
confidence: 97%
“…The mutant of Arabidopsis UGT74F2 , a glycosyltransferase, accumulates high levels of glycosylated nicotinate, and the mutant displayed decreased rates of seed germination, of which the germination drawback of the ugt74f2 mutant could be fully recovered by overexpressing UGT74F2 ( Li W. et al, 2015 ). Moreover, N-glycosylation mapping of rice embryos during germination has discovered 242 glycosites from 191 unique proteins, and these N-glycosylated proteins were enriched in starch and sucrose metabolism pathway, which were predicted to interact with several BR signaling proteins, implying that N-glycosylation is involved in carbohydrate metabolism and BR signaling to regulate seed germination ( Ying et al, 2017 ).…”
Section: Other Ptms Regulation Of Seed Germinationmentioning
confidence: 99%
“…However, N-and O-glycosylation are the most abundant in plants. It is estimated that approximately 50% of all proteins are glycoproteins, of which the majority is N-glycosylated [47,48]. The presence or absence of N-and O-glycans on glycoproteins has been shown to influence a proteins' activity, stability and functionality to a large extent, and plays a critical role in cellular signaling, molecular trafficking, plant development and adaptation to biotic and abiotic stresses [7,49,50] (Figure 1).…”
Section: Plant Development In a Nut Shellmentioning
confidence: 99%
“…Moreover, these mutations can also affect the germination stage [ 130 ] ( Figure 4 ). In germinating rice seeds, the number of N-linked glycosites equaled 242, distributed over 191 glycoproteins, highlighting the abundance and importance of (N-linked) glycosylation for the germinating seed [ 48 ]. Results of Horiuchi et al [ 243 ] indicate that the glycosylation pattern of ungerminated and germinated rice seeds changes.…”
Section: Developmental Consequences Of Glycosylation: From Flowers To Germinating Seedsmentioning
confidence: 99%